Comparing positive and negative beliefs about worry in predicting generalized anxiety disorder symptoms - Penney, Alexander; Mazmanian, Dwight; Rudanycz, Caitlin (My University, 2012)
People with generalized anxiety disorder (GAD) hold both positive and negative beliefs about worry. Dugas and Koerner (2005) view positive beliefs as one of the maintaining factors in GAD. Wells (2005) argues that the positive beliefs regarding worry are not unique to GAD, and that it is the negative beliefs about worry that maintain GAD. Ruscio and Borkovec (2004) found that the negative beliefs that worry is uncontrollable and dangerous differentiated individuals with GAD and individuals who were high worriers without GAD. The current study aimed to extend the findings of Ruscio and Borkovec (2004) through the use of a mediation model in a non-clinical sample (N = 230). Using subscales from the Why Worry-II (Holowka, Dugas, Francis, & Laugesen, 2000) and the Metacognitions Questionnaire-30 (Wells & Cartwright-Hatton, 2004), the results confirmed that both positive and negative beliefs about worry were correlated with GAD symptoms and trait worrying. However, using sequential regression, only the negative beliefs that worry is uncontrollable and dangerous, and that thoughts should be controlled predicted GAD symptoms after controlling for trait worrying. These beliefs, particularly the beliefs that worry is uncontrollable and dangerous, were found to mediate the relationship between trait worrying and GAD symptoms. Implications for models of the development of GAD are discussed.
Keywords: generalized anxiety disorder; worry; positive beliefs; negative beliefs; metacognition